Inhalációs eszközhasználattal összefüggő betegbiztonságot támogató betegoktatás megszervezése. - Zahorecz Gabriella (2017)
Adherence to the therapy of patients who are using inhalation devices is inadequate, this efficiency of the therapy is lower than the medically expected, which has negative clinical and health-economy consequences as well as incorporates hidden patient safety risks. The primary objective of the professional care staff to utilize medical interventions, which provide the greatest health benefits to the population and the patients suffering from the given chronic disease, but the available resources are limited. Improvement on the cooperation of the patients can be expected from those interventions, which have influence on several factors. These factors incorporates the following areas: the health condition of the patient, the social – economy factors, therapy dependent factors, the patient dependent factors, the factors depending of medical care and the care provider staff. The decreased patient cooperation is a main reason of therapeutic failure and this has pharmaco-economic consequences. The aim of this thesis, is to demonstrate, that by patient education, the cooperation and adherence of the patients suffering from chronic obstructive pulmonary disease can be improved on the usage of inhalation device therapy. By the timely recognition and treatment of the chronic disease, there is an opportunity to improve the condition of the patients, extend the life expectancy, decrease the patient safety risks, and by lifestyle changes (eg, quitting from smoking) quality of life can be significantly improved. The efficiency of all of these activities are corroborated by international data.